Free-living nitrogen fixation responds to elevated nutrient inputs in tropical montane forest floor and canopy soils of southern Ecuador - Burneo Valdivieso, J. (2015)
Although often overlooked in forest research, the canopy can play an important role in forest nutrient cycling. Since the canopy is spatially isolated from the forest floor, nutrient cycling in the two areas may differ as terrestrial nutrients accumulate. We measured rates of free-living N2 fixation along an elevation gradient (1,000, 2,000 and 3,000 m) of tropical montane canopy soils, compared these to rates measured in the top 5 cm of forest floor soils (excluding fresh litter), and assessed the effects of elevated nutrient inputs to the forest floor. N2 fixation was measured using the acetylene reduction assay. Measurements occurred in the field, in the wet and dry seasons, using intact cores of soil. The forest floor had been fertilized biannually with moderate amounts of nitrogen (N) and phosphorus (P) for 4 years; treatments included control, N, P and N + P. N2 fixation rates exhibited little variation with elevation but were higher in the dry season than the wet season. Fixation was inhibited in forest floor N plots compared to control and P plots, and stimulated in canopy P plots compared to control. At 2,000 m, the canopy contributed 12 % of measured canopy and forest floor N2 fixation (1.2 kg N ha?1year?1). Results suggest that N2 fixation is an active process in canopy soils, which is variable across seasons and sensitive to changes in terrestrial nutrient availability. Long-term terrestrial accumulation of N and/or P has the potential to significantly change the dynamics of soil N cycling in these canopies.